2016
DOI: 10.4103/1735-9066.193391
|View full text |Cite
|
Sign up to set email alerts
|

Validation of critical care pain observation tool in patients hospitalized in surgical wards

Abstract: Background:Application of a reliable and authentic behavioral tool for measuring patients’ pain, hospitalized in intensive care units who are not able to establish relationship, is needed severely. Therefore, this study is conducted with the aim of validating Critical Care Pain Observation Tool (CPOT) in patients hospitalized in surgical wards.Materials and Methods:CPOT was first translated into Persian and was psychometrically measured in terms of content.Results:It should be noted that the content validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…This tool has been reviewed and investigated in 22 studies on 1249 patients in various intensive care units such as medical, surgical, open-heart surgery, and neurosurgery [10], [15], [28], [29], [32], [33], [34], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This tool has been reviewed and investigated in 22 studies on 1249 patients in various intensive care units such as medical, surgical, open-heart surgery, and neurosurgery [10], [15], [28], [29], [32], [33], [34], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53].…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of the tool was examined in 18 studies [28], [29], [32], [33], [34], [39], [40], [41], [42], [43], [44], [45], [47], [49], [50], [51], [52], [53]. A test-retest procedure was then performed in one study with non-parametric Spearman correlation coefficient of 0.81-0.93, indicating the reliability of the primary test [49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This tool measures pain with four indicators, including facial expressions, body movements, muscle tonicity, and ventilator resistance, in critically-ill adult patients under mechanical ventilation and has a minimum score of zero and a maximum of eight. This tool was validated in 2006 by Gelinas et al [ 28 ] and its validity and reliability were confirmed in Iran by Rafiei et al in 2015 [ 29 ].…”
Section: Methodsmentioning
confidence: 97%